2010
DOI: 10.4274/turkderm.44.132
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dermatosis During Childhood

Abstract: SummaryBackground and Design: The aim of this study was to determine the distribution of skin diseases during childhood. Material and Method: A retrospective descriptive study was planned. Among 18318 patients referred to our dermatology outpatient clinic between September 2004 and November 2009, 1756 child patients between 0-12 years of age were retrospectively analyzed from automation record system. Results: A total of 1756 child patients who referred during the study period were included in the study; 791 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
(12 reference statements)
1
7
0
5
Order By: Relevance
“…Otros trastornos habituales fueron las dermatosis infecciosas (20,6%), los trastornos eritematosos escamosos (9,9%), la xerosis (7,8%) y los trastornos de la pigmentación (6,7%). 10 Tamer, et al realizaron un estudio en Angora, en el cual informaron que el acné vulgar, detectado en el 12,4% de la población del estudio, fue la enfermedad de la piel más frecuente en los niños, seguido de la dermatitis atópica (11,8%), la dermatitis de contacto (11,3%), las verrugas (9,5%) y el impétigo (4%). 11 Inanir, et al informaron los siguientes trastornos de la piel frecuentes en los niños de Manisa: nevos melanocíticos (14,4%), queratosis pilar (12,5%), pitiriasis alba (12%), xerosis (11,8%), pediculosis de la cabeza (9,4%) y dermatitis atópica (6,8%).…”
Section: Discussionunclassified
“…Otros trastornos habituales fueron las dermatosis infecciosas (20,6%), los trastornos eritematosos escamosos (9,9%), la xerosis (7,8%) y los trastornos de la pigmentación (6,7%). 10 Tamer, et al realizaron un estudio en Angora, en el cual informaron que el acné vulgar, detectado en el 12,4% de la población del estudio, fue la enfermedad de la piel más frecuente en los niños, seguido de la dermatitis atópica (11,8%), la dermatitis de contacto (11,3%), las verrugas (9,5%) y el impétigo (4%). 11 Inanir, et al informaron los siguientes trastornos de la piel frecuentes en los niños de Manisa: nevos melanocíticos (14,4%), queratosis pilar (12,5%), pitiriasis alba (12%), xerosis (11,8%), pediculosis de la cabeza (9,4%) y dermatitis atópica (6,8%).…”
Section: Discussionunclassified
“…Ülkemizde İzmir ve Zonguldak'ta yapılan çalışmalarda da en sık gözlenen hastalık grubu ekzemalar olarak bildirilmiştir. 1,2 Hindistan ve Etiyopya gibi ülkelerdeki çalışmalarda ise çocuklarda ekzemalardan farklı olarak ilk sırada enfeksiyon ve enfestasyon hastalıklarının olduğu görülmüştür. 3,6 Ülkemizde Antakya'da bir yetimhanede yaşayan çocuklarda enfeksiyöz hastalıklar ilk sırada saptanmıştır.…”
Section: Bulgularunclassified
“…Ülkemizdeki çalışmalarda da en sık görülen viral hastalık verruka olarak saptanmıştır. 1,11,22 Verruka tanısı alan hastalarımızın en sık okul dönemi ve adölesan dönemde olduğu belirlenmiştir. Yaş gruplarına göre görülme sıklığı diğer çalışmalarla benzer saptanmıştır.…”
Section: Bulgularunclassified
See 1 more Smart Citation
“…In this study, Skin infections and infestations, accounting for 47.15% of patients, were found to be the most common dermatologic diseases, [16]. Saçar et al reported infectious skin diseases as second most common disease group (20.6%) after eczema [17].…”
mentioning
confidence: 99%